Photosynthetic electron transport activity of light and shade-acclimated field grown grapevine leaves - Teszlák, Péter; Gaál, Krisztián; Kozma, Pál (Acta Biologica Szegediensis, 2007)
The light response curves of relativ e electron transport rate (ETR) in field grown grapevine (Vitis vinifer a L.) leaves were studied on different canopy exposure. The daily course of incident photosynthetic photon flux density (PPFD) was measured by means of ceptometer configured in segmented mode and inserted through the canopy. We compared the photosynthetic activity of shaded leaves and leaves exposed to sunlight on the eastern and western sides of canopy by North-South row direction. Moreover, we studied the seasonal influence of change in daily mean temperature and precipitation frequency on ETR light response curves. The different sides of canopy showed significant differences with regard the incident PPFD value, the western side received with 30% higher maximum PPFD values compared to eastern leaves. However, despite these differences we did not find any significant differences in the ETR light response curves between east and west-positioned leaves. The favourable water condition with lower daily mean temperature (<20°C) resulted in significant lower ETR values in all leaf types. Based on seasonal fluctuation of ETR light curves we can hypothesized that low temperature have higher impact on photosynthetic electron transport activities of grapevine leaves than moderate water deficit.